Discovery of Novel Benzo[a]phenoxazine SSJ-183 as a Drug Candidate for Malaria - Ge, Jian-Feng (American Chemical Society, 2010)
[Image: see text] Malaria is a serious infectious disease caused by protozoan parasites in tropical and subtropical regions. Even inhabitants of temperate zones are exposed to the danger of malaria infection because of travel and global warming. Novel, effective, safe, and inexpensive drugs are required to treat malaria and contribute to the global goal of eradication. A search for new antimalarial agents has been performed by the synthesis of new benzo[a]phenoxazines, followed by biological evaluations. The derivative SSJ-183 (5), having a 4-aminopyridine group, showed an IC(50) value against Plasmodium falciparum of 7.6 nM and a selectivity index of >7300. Cure was achieved by three oral doses of 5 at 100 mg/kg to mice infected with the Plasmodium berghei ANKA strain. The safety of 5 was supported by acute toxicity testing in mice with single doses up to 2000 mg/kg po, chromosome aberration test, in vitro as well as in vivo micronucleus tests, and phototoxicity studies in mice. Thus, 5 is a promising candidate as a new antimalarial agent.